Concurrent Bilateral Central Retinal Artery Occlusion Secondary to Sickle Cell Crisis - Gowri Renganathan MD; Piruthiviraj Natarajan MD; Lela Ruck MD; Roberto Prieto MD; Bharat Ved Prakash MD; Sudhagar Thangarasu MD, FACP (SAGE Publishing, 2021)
Vascular occlusive crisis with a concurrent vision loss on both eyes is one of the most devastating disability for sickle cell disease patients. Reportedly occlusive crisis in the eyes is usually temporary whereas if not appropriately managed can result in permanent vision loss. A carefully managed sickle cell crisis could prevent multiple disabilities including blindness and stroke. We report a case of a 24-year-old female with a history of sickle cell disease who had acute bilateral vision loss during a sickle crisis and recovered significantly with a timely emergent erythrocytapheresis.